Peri-ovarian adipose tissue contributes to intraovarian control during folliculogenesis in mice. Issue 2 (August 2018) - Yang, Liuhong; Chen, Lei; Lu, Xiaosheng; Tan, Anni; Chen, Yao; Li, Yalan; Peng, Xuemei; Yuan, Shaochun; Cai, Dongqing; Yu, Yanhong
Abstract : Peri-ovarian adipose tissue (POAT) is a kind of intra-abdominal white adipose tissue that is present surrounding the ovaries in rodents. Recent studies demonstrated that POAT-deficient mice displayed a phenotype of delayed antral follicular development, for which decreases in serum estrogen, serum FSH and FSHR levels were responsible. However, folliculogenesis is regulated by endocrine signals and also modulated by a number of locally produced intraovarian factors whose acts are both autocrine and paracrine. Here, we used a model of surgical removal of POAT unilaterally and contralateral ovaries as controls, as both were under the same endocrine control, to assess the paracrine effect of the POAT on folliculogenesis. Surgical removal of unilateral POAT resulted in delayed antral follicular development and the increased number of atretic follicles, accompanied by decreased levels of intraovarian adipokines and growth factors, lipid accumulation and steroidogenic enzyme expression. POAT-deficient ovaries displayed compensatory increased expressions of intraovarian genes, such as Vegf and Adpn for angiogenesis, Acc, Fasn, and Gapdh involved in lipogenesis and Fshr in response to FSH stimulation. Furthermore, we demonstrated that removal of POAT promoted follicular apoptosis, caused retention of cytoplasmic YAP and inhibited PTEN-AKT-mTOR activation. These alterations were observed only in the POAT-deficient ovaries but not in the contralateral ovaries (with POAT), which suggests that a paracrine interaction between POAT and ovaries is important for normal folliculogenesis.